EFFECTIVENESS EFFECTIVENESS OF THE GIVING STARFRUIT LEAF EXTRACT (AVERRHOA BILIMBI L.) AND CINNAMON (C. BURMANII) AS AN ALTERNATIVE TO ANTIBACTERIALS FOR THE HEALING OF PERINEUM WOUNDS IN RATTUS NORVEGICUS - Tiara Widiatami; Rasipin Rasipin; Diyah Fatmasari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Background: The prevalence of infections that occur during the puerperium is 7.3%, due to poor hygiene in wounds The perineum is one of the causes of bacterial proliferation. Pharmacological treatment with antibiotics results in resistance. Non-pharmacological treatment using starfruit leaf extract and cinnamon is a safer alternative solution to reduce the number of bacteria. Objective: To prove the effectiveness of giving starfruit leaf extract (Averrhoa Bilimbi L.) and cinnamon (C. Burmanii) as an antibacterial alternative to perineal wound healing in rats. Methods: True experiment the using study design pre-test post-test with control group. Data collection involved 5 rats, selected through probability sampling technique with method simple random sampling which was divided into 2 groups, namely the treatment group which was given a combination of starfruit leaf extract and cinnamon at a dose of 400 mg/kg rats (equivalent to 0.4 mg /gram body weight rats), while the control group was only given amoxicillin 0.045 mg/200 grams of body weight rats for 7 days. Results: There was a difference before and after giving of starfruit leaf extract and cinnamon on the REEDA scale score (p value <0.05) in the intervention group compared to the control group which was only given amoxicillin 0.045 mg/200 grams, then the t test showed no significant difference between the intervention group and the control group (p value > 0.05). Conclusion: The combination of starfruit leaf extract and cinnamon which was effective in healing perineal wounds based on the REEDA scale score compared to the control group, but was not effective in reducing the number of colonies of bacteria Staphylococcus Aureus.